1994
DOI: 10.3758/bf03211690
|View full text |Cite
|
Sign up to set email alerts
|

Haptic identification of curved surfaces

Abstract: In two experiments, the active haptic identification ofthree-dimensional mathematically welldefined objects is investigated. The objects, quadric surfaces, are defined in terms of the shape index, a quantity describing the shape, and curvedness, a quantity describing overall curvature. Both shape index and curvedness are found to have a significant influence on haptic shape identification. Concave surfaces lead to a larger spread in responses than convex ones. Hyperbolic surfaces show a slight tendency to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 15 publications
3
38
1
Order By: Relevance
“…How does performance in this environment compare with human performance at recognizing physical objects? Using a superset of the five shapes we selected for our benchmark, Kappers et al [2] found accuracy rates close to 100%. They do not report response times.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…How does performance in this environment compare with human performance at recognizing physical objects? Using a superset of the five shapes we selected for our benchmark, Kappers et al [2] found accuracy rates close to 100%. They do not report response times.…”
Section: Discussionmentioning
confidence: 97%
“…In another study, the same authors used a restricted set of objects which could not be readily distinguished by material properties, producing a shape recognition task [4]. Other researchers have used abstract stimuli for shape recognition tasks [2].…”
Section: The Shape Recognition Task and Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Koenderink (1990) sought to ground the understanding of visual shape perception in the principal curvatures defined at a surface point given the essential requirement of a quantification of shape that is independent of perspective (coordinate system) and scale. Consonant with Marr's (1982) proposal, Koenderink (see also Lehky & Sejnowski, 1990) tied the coordinate system for a shape to the shape itself, specifically, to its principal directions or eigenvectors and their magnitudes, the eigenvalues k^ and k min (for applications to haptic touch, see Kappers, Koenderink, & Lichtenegger, 1994;Kappers, Koenderink, & te Pas, 1994).…”
Section: Tangible Shape and Issues Of Shape Perceptionmentioning
confidence: 99%
“…Recently, we introduced a method to investigate haptic shape identification with the aid of mathematically well-defined objects (Kappers et al 1994). A series of quadric surfaces (including elliptical, hyperbolical, spherical, and cylindrical paraboloids) of varying curvature were used to determine performance in terms of percentage correct identification.…”
Section: Introductionmentioning
confidence: 99%